Sensorial Analysis of Wines from Malpighia glabra L. Pulp - Almeida, Sheyla dos Santos; Souza, de, Roberto Rodrigues; Santana, José Carlos Curvelo; Tambourgi, Elias Basile (Brazilian Journal of Operations & Production Management, 2010)
This work aimed to make the sensorial analysis of Barbados cherry (Malpighia glabra L.) wines. A standardized questionnaire was used to evaluate the effect of soluble solids (°Brix) and the concentration of fruit pulp on sensorial quality attributes (color, flavor and aroma) of wines; which were measured on hedonic scale, to obtain the best condition for manufacturing wine from Barbados cherry. Saccharomyces cerevisiae yeast was used for fermentation. Results showed that Barbados cherry wines were suave, sweet and with 11°GL of alcohol concentration. Flavor and color of wines were characteristic of acerola fresh fruit. The t Student test showed that did not present any significant difference among the wines in both these sensorial attributes. Increasing the initial °Brix of must, the wine obtained had better acceptance and there was no effect of pulp mass on sensorial attributes studied. Sensorial analysis revealed that the best Barbados cherry wine was obtained for a must with composition of 22 g/L of sugar and 1 kg of Barbados cherry pulp for each 6 liter of wine. This work supports the usage of acerola for obtaining high quality wines which possess pleasing aroma and shiny red color.